Conflict and cooperation in intelligence and security organisations an institutional costs approach - Thomson, James 1963- (Routledge, Taylor & Francis Group, 2022)
"This book provides an institutional costs framework for intelligence and security communities to examine the factors that can encourage or obstruct cooperation. The governmental functions of security and intelligence require various organisations to interact in a symbiotic way. These organisations must constantly negotiate with each other to establish who should address which issue, and with what resources. By coupling adapted versions of transaction costs theories with socio-political perspectives, this book provides a model to explain why some co-operative endeavours are successful, whilst others fail. This framework is applied to counterterrorism and defence intelligence in the UK and the US, to demonstrate that the view of good cooperation in the former and poor cooperation in the latter is overly simplistic. Neither is necessarily more disposed to behave cooperatively than the other; rather, the institutional costs created by their respective organisational architectures incentivises different cooperative behaviour in different circumstances. This book will be of much interest to students of intelligence studies, organisational studies, politics, and security studies"--
Keywords: Aufklärung -- Militär; Kooperation; Geheimdienst; Intelligence service / International cooperation; Military intelligence / International cooperation; Military intelligence / Great Britain; Military intelligence / United States; Military intelligence; Great Britain; United States